2014
DOI: 10.1063/1.4890612
|View full text |Cite
|
Sign up to set email alerts
|

Efficient allocation of heterogeneous response times in information spreading process

Abstract: Recently, the impacts of spatiotemporal heterogeneities of human activities on spreading dynamics have attracted extensive attention. In this paper, we intend to understand how the heterogeneous distribution of response times at the individual level influences information spreading. Based on the uncorrelated scale-free networks without degree-degree correlation, we study the susceptible-infected spreading dynamics with adjustable power-law response time distribution, and find that the stronger the heterogeneit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Model (2) offers a cognition of the propagation of epidemics, information and financial risk in complex systems. Since many real applications, such as infectious disease [ 19 ], information propagation [ 21 ], computer virus [ 26 ] and financial risks transmission [ 27 ] are all correlated with the epidemic dynamics on networks, more detailed justifications for epidemiology on networks have been carried out by some researchers, among which are J. Zhang et al [ 3 ] and Y. Wang et al [ 8 ], M. Small [ 18 , 19 ], M. Newman [ 28 ], A. Cui et al [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Model (2) offers a cognition of the propagation of epidemics, information and financial risk in complex systems. Since many real applications, such as infectious disease [ 19 ], information propagation [ 21 ], computer virus [ 26 ] and financial risks transmission [ 27 ] are all correlated with the epidemic dynamics on networks, more detailed justifications for epidemiology on networks have been carried out by some researchers, among which are J. Zhang et al [ 3 ] and Y. Wang et al [ 8 ], M. Small [ 18 , 19 ], M. Newman [ 28 ], A. Cui et al [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both Monte Carlo simulations [14][15][16][17] and theoretical study [18] have investigated the effects of network structures on epidemic spreading velocity [19,20], epidemic variability [21,22], epidemic size [23][24][25][26][27][28], and epidemic thresholds [29][30][31][32][33][34]. Both the epidemic size and threshold can indicate the probability of an epidemic occurring [32], which seeds are influential [35][36][37][38], and how to effectively control the epidemic once it begins [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Specially, for scale-free networks with degree exponent γ ≤ 3, the outbreak threshold vanishes in the thermodynamic limit [18,19,24,25]. Further studies revealed that the degree heterogeneity promotes spreading outbreaks, however limits the outbreak size at large transmission rates [13].Utilizing network information to effectively enhance the spreading speed and outbreak size is an important topic in spreading dynamics studies [26][27][28][29][30]. The studies on effective information spreading can provide inspiration for epidemic controlling [31][32][33], as well as marketing strategies optimization [34][35][36].…”
mentioning
confidence: 99%
“…Utilizing network information to effectively enhance the spreading speed and outbreak size is an important topic in spreading dynamics studies [26][27][28][29][30]. The studies on effective information spreading can provide inspiration for epidemic controlling [31][32][33], as well as marketing strategies optimization [34][35][36].…”
mentioning
confidence: 99%